Sirolimus: A Successful Medical Treatment for Head and Neck Lymphatic Malformations - Steven Curry; Andrew Logeman; Dwight Jones (Case Reports in Otolaryngology)
Lymphatic malformations are abnormalities that arise in the developing lymphatic system, most frequently presenting in the head and neck. They are typically treated with sclerotherapy, laser therapy, or surgery for localized lesions. Sirolimus, an inhibitor of the mammalian target of rapamycin, is a relatively new medical therapy for the treatment of vascular malformations. This case report presents the improvements and complications seen in a female infant who was diagnosed with a large lymphatic malformation on prenatal ultrasound and has been treated with sirolimus during the first 9 months of life.